Dual Antigen T Cell Engagers Targeting CA9 as an Effective Immunotherapeutic Modality for Targeting CA9 in Solid Tumors - Tatari, Nazanin; Zhang, Xiaoyu; Chafe, Shawn C.; McKenna, Dillon; Lawson, Keith A.; Subapanditha, Minomi; Shaikh, Muhammad Vaseem; Seyfrid, Mathieu; Savage, Neil; Venugopal, Chitra; Moffat, Jason; Singh, Sheila K. (Frontiers in Immunology, 2022)
Glioblastomas (GBM), the most common malignant primary adult brain tumors, are uniformly lethal and are in need of improved therapeutic modalities. GBM contain extensive regions of hypoxia and are enriched in therapy resistant brain tumor-initiating cells (BTICs). Carbonic anhydrase 9 (CA9) is a hypoxia-induced cell surface enzyme that plays an important role in maintenance of stem cell survival and therapeutic resistance. Here we demonstrate that CA9 is highly expressed in patient-derived BTICs. CA9 + GBM BTICs showed increased self-renewal and proliferative capacity. To target CA9, we developed dual antigen T cell engagers (DATEs) that were exquisitely specific for CA9-positive patient-derived clear cell Renal Cell Carcinoma (ccRCC) and GBM cells. Combined treatment of either ccRCC or GBM cells with the CA9 DATE and T cells resulted in T cell activation, increased release of pro-inflammatory cytokines and enhanced cytotoxicity in a CA9-dependent manner. Treatment of ccRCC and GBM patientderived xenografts markedly reduced tumor burden and extended survival. These data suggest that the CA9 DATE could provide a novel therapeutic strategy for patients with solid tumors expressing CA9 to overcome treatment resistance.